Research on Thermal Performance of Polypropylene Fiber-Reinforced Concrete Wall Panels - Zhe Zhang; Yiru Hou; Yi Wang (Buildings, 2025)
The global construction industry faces pressing challenges in enhancing building energy efficiency standards. To address this critical issue, facilitate worldwide green and low-carbon transformation in construction practices and improve the thermal performance of building wall panels to achieve optimal levels, a novel polypropylene fiber-reinforced concrete wall panel has been developed and investigated. A three-dimensional steady-state heat transfer finite element model of the wall panel was established to simulate its thermal performance. Key parameters, including the thickness of the inner and outer concrete layers, insulation layer thickness, connector spacing, and connector arrangement patterns, were analyzed to evaluate the thermal performance of the fiber-reinforced concrete composite sandwich wall panel. The results indicate that the heat transfer coefficients of the G-FCSP and FCSP wall panels were 0.768 W/m2 · K and 0.767 W/m2 · K, respectively, suggesting that the glass fiber grid had a negligible impact on the thermal performance of the panels. The embedded insulation layer was crucial for enhancing the thermal insulation performance of the wall panel, effectively preventing heat exchange between the two sides. Increasing the thickness of the concrete layers had a very limited effect on reducing the heat transfer coefficient. Reducing the spacing of the connectors improved the load-bearing capacity of the composite wall panel to some extent but had minimal influence on the heat transfer coefficient; to achieve optimal performance by balancing structural load distribution and thermal damage resistance, a connector spacing ranging from 200 mm to 500 mm is recommended. The variation in heat transfer coefficients among the four different connector arrangement patterns demonstrated that reducing the thermal conduction media within the wall panel should be prioritized while ensuring mechanical performance. It is also recommended that the connectors are arranged in a continuous layout.